2018
DOI: 10.1080/09613218.2018.1501873
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Petri-net models to predict the degradation of ceramic claddings

Abstract: In this study, a stochastic Petri net formalism is proposed to predict the degradation of ceramic claddings over time to understand how different environmental exposure conditions contribute to the overall degradation of these claddings. For that purpose, the degradation condition of 195 ceramic claddings located in Lisbon (Portugal) is evaluated through in situ visual inspections. In the first part of the study, a stochastic deterioration Petri net model is proposed to the entire sample. In the second part, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Among the four constructive solutions, the main observations are different, and it is concluded that solar exposure has different impacts according to the solution adopted. This is in line with the results obtained in previous studies [7,17,39,40,[73][74][75]:…”
Section: Orientationsupporting
confidence: 93%
See 4 more Smart Citations
“…Among the four constructive solutions, the main observations are different, and it is concluded that solar exposure has different impacts according to the solution adopted. This is in line with the results obtained in previous studies [7,17,39,40,[73][74][75]:…”
Section: Orientationsupporting
confidence: 93%
“…The optimal parameters of the degradation process are presented in Table 1, in terms of mean and standard deviation of the sojourn time in each degradation condition. The fit of the degradation process to the historical data (collected through in-situ visual inspections) was performed through a degradation model based on stochastic Petri nets, in which the choice of the best probability distribution that describes the degradation process is performed through the maximization of the logarithm of the likelihood [17]. The information presented in this table can be read in the following way: For a CTS, for the situation without impact of the environmental exposure conditions, a transition between conditions A and B, T A , takes, on average, 6.6 years to occur, with a standard deviation of 6.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations